2018
DOI: 10.1074/jbc.m117.789503
|View full text |Cite
|
Sign up to set email alerts
|

Controlled dimerization of insulin-like growth factor-1 and insulin receptors reveals shared and distinct activities of holo and hybrid receptors

Abstract: Breast cancer development and progression is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…On one hand, IGF‐2R acts as a scavenger for circulating IGF‐2 and is not targeted by AG‐1024, whereas activation of IGF‐1R by IGF‐2 activates signaling leading to proliferation, survival and other downstream events . In addition, it was recently shown that proliferation is principally mediated by IGF‐1R as homodimers or as hybrid IGF‐1R/INSR receptors rather than through the INSR, and that prosurvival activity was mainly provided by homo IGF‐1R . Enhanced IGF‐1R signaling in CB CD34 + cells may be responsible for the enhanced expansion of PEP in OCM cultures.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, IGF‐2R acts as a scavenger for circulating IGF‐2 and is not targeted by AG‐1024, whereas activation of IGF‐1R by IGF‐2 activates signaling leading to proliferation, survival and other downstream events . In addition, it was recently shown that proliferation is principally mediated by IGF‐1R as homodimers or as hybrid IGF‐1R/INSR receptors rather than through the INSR, and that prosurvival activity was mainly provided by homo IGF‐1R . Enhanced IGF‐1R signaling in CB CD34 + cells may be responsible for the enhanced expansion of PEP in OCM cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al researched on the insulin receptor pathway and were able to differentiate between the insulin receptor types of the insulin-like growth factor receptor 1 (IGF1R) and the insulin receptor (InsR) as well as the respective hybrid of the heterodimer of both (HybR). The bivalent homodimerizer AP20187 and the heterodimerizer AP21967 were used as CIDs (Chen et al, 2018).…”
Section: Chemical Tools/chemically Induced Dimerization Utilizing Fkbpsmentioning
confidence: 99%
“…Both IR-A/IGF-IR (Hybrid A) as well IR-B/IGF-IR (Hybrid B) receptors can be formed [ 27 ]. The biological functions of these hybrids remain uncertain without examining cells not expressing holo-IGF-IR or holo-IR [ 28 ]. Nevertheless, it has been suggested that IR/IGF-IR hybrids act in a manner similar to that of IGF-IR.…”
Section: Biology Of Insulin-like Growth Factor (Igf) Family and Thmentioning
confidence: 99%
“…Nevertheless, it has been suggested that IR/IGF-IR hybrids act in a manner similar to that of IGF-IR. Hybrid receptors respond more predictably to IGF-I than to insulin under physiological conditions [ 28 , 29 ]. They may account, at least in part, for the overlapping yet distinct actions of the two ligands.…”
Section: Biology Of Insulin-like Growth Factor (Igf) Family and Thmentioning
confidence: 99%
See 1 more Smart Citation